DESAIN SISTEM PENJAMINAN MUTU PADA SATUAN PENDIDIKAN TAMAN KANAK-KANAK (TK) - Nisa Islami (EARLY CHILDHOOD : JURNAL PENDIDIKAN, 2018)
This paper will substantially discuss the quality assurance system in the kindergarten education unit. This matter becomes very important because the education unit of kindergarten to date hasn’t yet implemented the optimal quality assurance system. Though kindergarten as the foundation of early education level is very effective role in developing intellectual, emotional, social and spiritual intelligence. Thus, the kindergarten education unit absolutely requires a serious quality management system that is managed seriously to direct and control educational programs in accordance with the policy direction, objectives, plans, and processes or quality procedures and their achievements in a sustainable manner. The implementation of quality assurance in the kindergarten education unit is done through: first, designing institutional quality assurance unit. Second, formulate the vision, mission, objectives and target institutions. Third, develop the Master Plan for Development, Strategic Plan and Operational Plan. Fourth, compile quality documents. Fifth, conduct an internal quality audit.